Penerapan Metode Eksperimen Pada Mata Pelajaran IPA Materi Sifat Cahaya Sekolah Dasar - Okpatrioka Okpatrioka; Ari Nusantari (ARKA INSTITUTE, 2022)
Based on the formulation of the problem in this study, how is the teacher's understanding of the experimental method, how is the use of media, how is the classroom atmosphere with the experimental method. This study aims to describe the knowledge of the teacher's understanding of the experimental method, to describe how to use the media, to describe the classroom atmosphere with the experimental method. This research is a library research which is conducted in a descriptive qualitative manner which is to facilitate researchers in collecting descriptive data in the form of written/oral words from the teachers and students who were observed. One of the research literature (library research) retrieval of data or materials needed to complete the study came from the library, including books, dictionaries, journals, documents, magazines and so on. Criteria used to select reading materials that relevance (relevance). . Except for historical research, should avoid the use of reading materials that are already old and more recent selected sources. . Source that has long been possible to load the theories or concepts that are no longer valid, because kebenarnnya theory has more recent research results. The results of the teacher's research have maximally applied the experimental method to the properties of light, thus the teacher has implemented it according to the concept of knowledge about the experimental method. Thus, it can be concluded that the application of the experimental method has been maximized so that the teacher can describe the properties of light SD.